An Adaptive LSB-Based Video Steganography Framework with Blockchain-Enabled Verification for Secure Multimedia Communication - Sumana, S. G.; Rajesh, T. M.; Shaila, S. G. (Engineering, Technology & Applied Science Research, 2026)
Digital communication systems face an ongoing major challenge to protect video information from unauthorized access, tampering, and eavesdropping operations. Standalone steganographic methods face two major drawbacks: restricted data storage capabilities and decreased ability to remain undetectable. This study presents an integrated video security framework that unites adaptive video steganography with hybrid cryptographic encryption and blockchain-enabled verification to protect data confidentiality, robustness, and integrity. The proposed framework consists of three separate modules that work together: StegoVision, Robust Video Steganography with Decoy Extraction, and Blockchain-Enabled Encryption. The StegoVision module uses an adaptive Least-Significant Bit (LSB) based embedding scheme with multi-stage compression to enable high-capacity covert communication. The system uses AES-CBC encryption with Knight’s Tour-based adaptive embedding and deception techniques to protect unauthorized extractors from detecting hidden data. The system uses hybrid AES-RSA encryption with IPFS-based decentralized storage to achieve tamper-proof authentication and traceability. The proposed method was tested on the HMDB51 (Human Motion DataBase) benchmark dataset. The StegoVision system achieved 94.1% accuracy through its visual quality preservation during compression and format conversion processes. The decoy-based model achieved 42.6 dB PSNR and 0.981 SSIM during compression and format conversion processes. The blockchain module achieved encryption speeds up to 320 MB/s with near-lossless reconstruction (PSNR > 51.4 dB, SSIM ≈ 0.999) and integrity verification accuracy exceeding 99.9%. A comparative analysis demonstrates that the proposed framework achieves an optimal balance between capacity, imperceptibility, robustness, and verifiability.